Adipose Triglyceride Lipase Is Implicated in Fuel- and Non-fuel-stimulated Insulin Secretion - Peyot, Marie-Line (American Society for Biochemistry and Molecular Biology, 2009)
Reduced lipolysis in hormone-sensitive lipase-deficient mice is associated with impaired glucose-stimulated insulin secretion (GSIS), suggesting that endogenous β-cell lipid stores provide signaling molecules for insulin release. Measurements of lipolysis and triglyceride (TG) lipase activity in islets from HSL(−/−) mice indicated the presence of other TG lipase(s) in the β-cell. Using real time-quantitative PCR, adipose triglyceride lipase (ATGL) was found to be the most abundant TG lipase in rat islets and INS832/13 cells. To assess its role in insulin secretion, ATGL expression was decreased in INS832/13 cells (ATGL-knockdown (KD)) by small hairpin RNA. ATGL-KD increased the esterification of free fatty acid (FFA) into TG. ATGL-KD cells showed decreased glucose- or Gln + Leu-induced insulin release, as well as reduced response to KCl or palmitate at high, but not low, glucose. The K(ATP)-independent/amplification pathway of GSIS was considerably reduced in ATGL-KD cells. ATGL(−/−) mice were hypoinsulinemic and hypoglycemic and showed decreased plasma TG and FFAs. A hyperglycemic clamp revealed increased insulin sensitivity and decreased GSIS and arginine-induced insulin secretion in ATGL(−/−) mice. Accordingly, isolated islets from ATGL(−/−) mice showed reduced insulin secretion in response to glucose, glucose + palmitate, and KCl. Islet TG content and FFA esterification into TG were increased by 2-fold in ATGL(−/−) islets, but glucose usage and oxidation were unaltered. The results demonstrate the importance of ATGL and intracellular lipid signaling for fuel- and non-fuel-induced insulin secretion.